Going into hak: Pathways for revitalizing marine tenure rights in Indonesia. (1st December 2021) - Muawanah, Umi; De Alessi, Michael; Pomeroy, Robert; Kurniasari, Nendah; Shafitri, Nensyana; Yulianty, Christina
Abstract: Marine conservation in Indonesia is complicated by the 1, 000s of islands and nearly as many languages and cultures that stretch across this 3200 mile (5100 km) country. Secure marine tenure has improved the prospects for sustainable fishing and livelihoods in many places around the world, and there are some traditional, historical examples of tenure in Indonesia. Where tenure institutions exist, however, they have typically been undermined by colonial and post-colonial policies, and in the vast majority of places, marine tenure and other rights (hak) to marine resources have either been extinguished or never existed. The issue is fraught: tenure rights may provide communities with the security to invest in and manage their fishery resources for long-term sustainability, but there is also a history in Indonesia of disenfranchisement in the name of conservation. This paper considers pathways to revitalizing marine tenure rights in Indonesia, documenting the evolution and current status of marine tenure rights in Indonesia, existing legal and policy frameworks that support marine tenure rights, and challenges to marine tenure rights. The paper concludes with recommendations for strengthening and expanding marine tenure rights in Indonesia and prospects for the development of a national policy on marine tenure rights. Highlights: History of Marine tenure rights in Indonesia. Legal and regulatory environment for marine tenure rights. Pathways for Revitalizing marine tenure in Indonesia.